2018
DOI: 10.4103/sni.sni_234_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparing deep brain stimulation in the ventral intermediate nucleus versus the posterior subthalamic area in essential tremor patients

Abstract: Background:The ventral intermediate nucleus (VIM) is the most commonly used target for deep brain stimulation (DBS) in patients with essential tremor (ET). Recent evidence suggests that the posterior subthalamic area (PSA) might be a better target for tremor reduction. We compared the outcome of VIM DBS with PSA DBS in our cohort of patients.Methods:Overall, 19 ET patients with bilateral DBS were included in this retrospective study, with a total of 38 electrodes (12 located in the VIM, 12 in the PSA, and 14 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Small, medium, and high differences between the means of the pair distributions are color coded in yellow, light red, and dark red, respectively. software 44,59 or classic stereotactic atlases; 19,50 thus our analysis based on validated MNI atlases may be considered more advanced. On the other hand, the distance from the active contact might seem to be a surrogate marker of target structure stimulation if it is compared with the surface covered by stimulation volume.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Small, medium, and high differences between the means of the pair distributions are color coded in yellow, light red, and dark red, respectively. software 44,59 or classic stereotactic atlases; 19,50 thus our analysis based on validated MNI atlases may be considered more advanced. On the other hand, the distance from the active contact might seem to be a surrogate marker of target structure stimulation if it is compared with the surface covered by stimulation volume.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Blomstedt et al [16] also reported that the total score of the tremor was reduced to 60% from baseline to 1-year follow-up; in particular, 95% improvement was seen in the tremor of the upper extremity, accompanied by 66% improvement in activities of daily living. When comparing VIM and PSA as optimal targets for tremor, previous studies have shown that they are not superior in reducing tremor [17]. However, a randomized, double-blind, crossover trial by Barbe et al [18] identified that PSA DBS is equally effective and more efficient than VIM DBS after 1-year-use.…”
Section: B Amentioning
confidence: 99%
“…Since 2012, several studies have proposed that PSA/cZi is a better target than Vim for tremor alleviation [ 10 , 11 , 12 , 13 ]. However, in 2018, two observational studies suggested that Vim-DBS might be more efficient in reducing tremors, and might provide better long-term outcomes than PSA/cZi-DBS [ 14 , 15 ]. Importantly, a randomized double-blind crossover trial performed by Barbe et al suggested that PSA–DBS is equally as effective as Vim-DBS [ 16 ].…”
Section: Introductionmentioning
confidence: 99%